"Now Is the Time to Wake Up": Islamic State's Narratives of Political Awareness. Issue 6 (18th August 2021) - Al-Dayel, Nadia
ABSTRACT: Terrorist organisations are increasingly seeking to attract transnational membership. In particular, the Islamic State proudly displays transnational support in its propaganda. As a result, academics have established that themes of belonging, religious fulfilment, victimhood and utopia are important recruitment devices. This article reveals additional themes that encourage a critical reasoning of the power dynamics in the citizen-state relationship, questioning the strength of religious ideology that is assumed to attract and bind transnational membership. These themes are revealed through an innovative, blended method of critical discourse analysis, interpretivism and securitisation that examines the narratives and influence of the recruitment actor on an international scale. After a review of the Islamic State's media operations, this method is applied to a prominent video featuring a top recruiter and UN designated terrorist, Australian citizen Neil Christopher Prakash. Then, it details how Prakash's migration to the Islamic State led to securitisation discourses from both Australia and the U.S., affecting citizen-state relations. It concludes with a discussion on implications, suggesting directions for research on transnational extremist organisations.